37 CORRELATION BETWEEN HYPERTONIC SALINE PD20 AND METHACHOLINE PC20 IN ASTHMA. (1st March 2006) - Kazani, S.; Sadeh, J.; Bunga, S.; Khan, N.; Wechsler, M. E.; Deykin, A.; Israel, E.
Abstract : Aim: Studies have reported contradictory results on the relationship between airway hyperresponsiveness to methacholine (Mch) and that elicited by hypertonic saline (HS) inhalation. We investigated the correlation between Mch-PC20 and HS-PD20 in mild asthmatics who had performed both challenges in a research setting. Methods: We assembled data on mild asthmatics on prn b-agonists, with a history of positive response to Mch (PC20 ≥ 8 mg/mL), who had undergone a staged 3% saline challenge. Mean time between challenges was 23 months (range 0.1-74, SD 21). We also compared the bronchial reactivity to exhaled breath condensate (EBC) pH, a putative marker of airway inflammation. Results: Subject data: Of the 24 subjects, 16 (67%) were responsive to the HS challenge. Nonresponders were assigned an HS-PD20 value of 74 mL. HS-PD20 correlated significantly with Mch-PC20 ( r = .52, p = .0089). EBC pH did not have a significant relationship with either HS-PD20 or Mch-PC20. Conclusion: HS and Mch reactivity provide similar assessments of airway reactivity in asthmatics not on controller medications. Considering the stability of the correlation, these data suggest that HS may be a substitute for Mch challenge. Neither measure of hyperresponsiveness correlates with EBC pH.